The Effects of a New Public Medicine Procurement Policy on Medicine Price in Shaanxi Province, Western China: An Interrupted Time Series Analysis - Hu, Shuchen; Chen, Chen; Yuan, Shengfang; Xue, Fei; Shi, Li; Fang, Yu; Yang, Caijun (Frontiers in Pharmacology, 2019)
Objectives To assess the effects on medicine price - a new public medicine procurement policy（NPMPP） undertaken in China in 2015. Methods An interrupted time series was used to evaluate the impact of NPMPP on the prices of emergency medicines, gynaecological medicines and paediatric medicines in Shaanxi Province, western China. Based on the procurement records in all the public health institutions in Shaanxi Province, we built three regression models. The monthly average price growth rate of the three categories of medicines was analysed covering the period 2015 to 2017. Findings Before the intervention, there was an increasing trend in the monthly average growth rate of the three categories of medicines, but only significant in emergency medicines and paediatric medicines. After the introduction of NPMPP, the increasing trend was accelerated for both the emergency medicines (coefficient = 0.114, P < 0.001) and gynaecological medicines (coefficient = 0.078, P < 0.05). While the increasing trend for paediatric medicines was slowed down after the intervention (coefficient = -0.024, P < 0.05). Conclusion By interrupted time series analysis, we identified a statistically significant increase in the price growth rate of emergency medicines and gynaecological medicines, but a statistically significant decrease in the price growth rate of paediatrics, following the introduction of NPMPP. And the impact of NPMPP on emergency medicines was greater than that on gynaecological medicines. To inhibit the growth trend of drug price, effective policies need to be introduced.